Distant-Source Swells Cause Coastal Inundation on Fiji’s Coral Coast - Wandres, Moritz; Aucan, Jérôme; Espejo, Antonio; Jackson, Naomi; De Ramon N’Yeurt, Antoine; Damlamian, Hervé (Frontiers in Marine Science, 2020)
Distant-source swells are known to regularly inundate low-lying Pacific Island communities. Here we examine extreme total water level (TWL) and inundation, driven by a distant-source swell on Fiji’s Coral Coast using observations and a phase-resolving wave model (XBeach). The objective of this study is to increase understanding of swell-driven hazards in fringing reef environments, to identify the contribution of wave setup and infragravity waves to extreme TWL, and to investigate coastal flooding during present and future sea levels. The maximum TWL near the shore was caused by compounding mechanisms, where tides, wave setup, infragravity waves, and waves in the sea swell frequencies contributed to the TWL. Waves and wave setup on the reef were modulated by offshore wave heights and tides, with increased setup during low tide and increased wave heights during high tide. Numerical simulations were able to reproduce the mechanisms contributing to the extreme TWL and allowed an estimation of the inundation extent. Simulations of the same swell under the RCP8.5 sea-level rise scenario suggested the area of inundation would increase by 97% by 2100. A comparison between the numerical model, a multiple linear regression model, and two commonly used parametric models revealed that both XBeach and the linear regression model were better suited to reproduce the nearshore wave setup and TWL than the empirical equations. The results highlight the need for customized, site-specific coastal hazard assessments and inundation forecast systems in the South Pacific.